Lifespan Human Function and Occupation - Cronin, Anne F. (New York : Routledge, 2025)
Lifespan Human Function and Occupation provides allied health students with a thorough and nuanced understanding of human development through a unique multi-dimensional framework, including biological, psychological, and sociological perspectives, which can then be translated into best-practice in their professional careers. The book is divided into three complementary sections. Section 1 provides a thorough overview to the key concepts within occupational science, before introducing the life course perspective, detailing individual developmental theories in context with social and environmental determinants of health, as well as presenting Bronfenbrenner's bioecological theory to illustrate the overarching role of culture in the development process. The following section explores nine distinct life stages, from prenatal and infancy to parenthood and fragile adulthood, with each chapter providing a thorough profile informed by the theoretical building blocks of Section 1. There is discussion of key issues such as substance abuse, job insecurity, working life conditions, early childhood development, structural racism, and impacts of COVID-19. The final section of the book, meanwhile, explores developmental differences and unpredictable, non-normative influences, such as trauma and developmental disability. This section includes a chapter focused on disability advocacy, as well as a chapter on neurodevelopmental disabilities. With each chapter featuring a range of pedagogical features, including learning objectives, case examples, and review questions, this comprehensive textbook will be essential reading for students across occupational therapy, physical therapy, athletic training, and other healthcare and rehabilitation disciplines, as well as those studying public health.
Section 1 The Life Course Perspective1 Multidimensional Development2 Environmental Contexts of Health3 Societal Perspectives of Populations and HealthSection 2 Life Stages4 Occupational Science and Theoretical Foundations5 Prenatal and Infant DevelopmentAppendix Postural Infant Reflexes6 The Preschool YearsAppendix Communication7 Middle and Late Childhood8 Adolescence9 Emerging Adulthood10 The Family and Parenthood11 Maturity: Early and Middle AdulthoodAppendix Loneliness12 Late AdulthoodSection 3 Disability Across the Life Span13 Fragile Adulthood14 Public Policy and Disability15 Neurodevelopmental Differences16 End of Life
Keywords: Human ecology; MEDICAL / Allied Health Services / Occupational Therapy